Thermal comfort of Frail People under dynamic and non-uniform thermal environments using a thermal manikin with thermoregulatory control: An experimental study - El akili, Zoubayre; Bouzidi, Youcef; Merabtine, Abdelatif; Polidori, Guillaume; Kauffmann, Julien (Energy and Built Environment, 2022)
The thermal comfort of frail people has to be considered carefully, mainly because of the high thermal sensitivity of this population and the negative influences that unsatisfactory thermal conditions have on their health. Most existing thermal comfort works have been conducted under steady-state, uniform thermal environments, with far fewer being performed in dynamic and non-uniform thermal environments, and even less for frail people. This study aimed at assessing the thermal responses of frail people under transient and non-uniform thermal environments, using a thermal manikin and a climatic test cell. Thermal responses were investigated and discussed in both genders. The analysis of variance showed a significant difference in thermal comfort and thermal sensation between females and males over time, under hot exposure. Under cold exposure, results showed a significant difference in thermal sensation between females and males over time, but no significant difference was observed in term of thermal comfort. Analysis revealed also significant differences in the dynamic thermal sensation between the sexes under cold exposure, while results confirmed that there is no significant difference in the dynamic thermal sensation between sexes under hot exposure.
Keywords: Building; Energy conservation; Thermal comfort; Thermal manikin; Thermal sensation